Simulação e gestão da disponibilidade hídrica em bacia hidrográfica representativa do bioma Cerrado - Gotardo, Jackeline Tatiane (2011)
The simulation study of water availability and management of the basin was addressed in two ways. First estimate the water demand in climatological experimental catchment representative of the Savannah. Defined by the difference in the occurrence of potential evapotranspiration and precipitation minimal likely to occur on a scale ten days. In the estimation of potential evapotranspiration compared to the empirical equations of the methods Blaney-Criddle, Hargreaves, ASCE Penman-Monteith, Penman, Priestley-Taylor method with the standard Penman-Monteith FAO 56. The method presented Blaney-Criddley is recommended when there is limited availability of climatological data. To estimate the probability distribution used the gamma distribution for the time series of precipitation and evapotranspiration and precipitation time series with zero values, we used the incomplete gamma function. The adhesion of the estimated probabilities to the observed data was verified by testing, non-parametric Kolmogorov-Smirnov test, with significance level (α-0, 05) which fitted well the model distributions. The occurrence of precipitation and evapotranspiration decendial likely P (X ≥ x) for different probability levels showed drought periods of ten days between 4:32, with critical values 25-39 mm, on a scale ten days, the months from May to September. In a second stage it was considered the the reservoir of soil water management and proposes a model allowing to calculate the irrigation water demand of crops of beans and corn planting dates in two different in drought and rainy. The bowl was hydrology by the method of the turn number (CN). Simulated the water demand and availability required in ascertaining what is the risk of meeting the irrigated area. The proposed model was effective for water management in the basin throughout the year. It was found that corn and beans require different amounts of water throughout the year, and that optimizing the additional water demand is a management tool able to minimize conflicts over water use. hydrology of the basin presents risks of not having met the demand required in the dry period is necessary to establish infraestrurura water for water storage